Analisis Filosofis terhadap Persepsi “Matematika Itu Sulit” dan Implikasinya terhadap Motivasi Belajar Siswa - Nur Elda Azaria; Reynata Tri Putri Apriliana; Anggun Badu Kusuma (Griya Journal of Mathematics Education and Application, 2026)
This article examines the philosophical belief that "mathematics is difficult" and how it affects students' motivation to learn. By looking at numerous scientific sources about students' perspectives, learning motivation, and mathematical philosophy, the study uses a literature review methodology. The results show that both internal and external influences affect the impression of mathematics as a challenging subject. Low self-esteem, anxiety about maths, a lack of basic abilities, a fear of failing, and bad learning experiences are examples of internal issues. Lack of parental support, academic pressure, boring instructional strategies, and the negative social stigma associated with mathematics are examples of external causes. Four philosophical schools of thought—formalism, constructivism, logicism, and intuitionism—can be used to understand this perception. Negative judgements also dramatically lower kids' drive to learn, which results in passive behaviour, low self-esteem, and poor academic achievement. Positive views, on the other hand, can improve motivation, critical thinking, and problem-solving skills. Therefore, improving students' views and motivation requires developing relevant, participatory, and student-centered mathematics instruction.